VALIDITAS BAHAN AJAR INTERAKTIF MATERI KLASIFIKASI DAN CIRI-CIRI HEWAN DALAM PEMBELAJARAN IPAS KELAS III SDN 03 PONTIANAK KOTA - Winata, Windy; Irfan Izudin, Muhammad; Kresnadi, Hery (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the content validity of the InterAnimalia interactive teaching material for the Ilmu Pengetahuan Alam dan Sosial (IPAS) subject on the topic of animal classification and characteristics for third-grade students at SDN 03 Pontianak Kota. The study was motivated by the limited use of interactive teaching materials in the learning process, which resulted in low student interest and participation in understanding IPAS content. The research employed the Research and Development (R&D) method using the ADDIE model, which consisted of the analysis, design, and development stages. The study focused on evaluating the content validity of the InterAnimalia interactive teaching material. The validation process was conducted by two validators, each assessing the material and media aspects of the product. The validation results indicated that the InterAnimalia interactive teaching material was categorized as highly valid. The material aspect obtained an Aiken’s V coefficient of 0.96, while the media aspect obtained an Aiken’s V coefficient of 0.98. Based on these findings, it can be concluded that the InterAnimalia interactive teaching material possesses a very high level of content validity in terms of both material and media aspects, making it suitable for product try-out.